Personal financial planning among adult learners / Masitah Hashim, Haziah Jamaludin and Fadzilah Azam Ahmad - Hashim, Masitah; Jamaludin, Haziah; Azam Ahmad, Fadzilah (Institute of Education Development (InED), 2007)
Planning for a secure financial future is not an easy task. This is because as an adult learner, one may save to buy one's first house, starting one's own business, pay for one's children education and setting enough retirement plans to maintain one's standard of living after retirement. Complex financial investments and changing tax laws will make it difficult to plan financially. We need to plan for tomorrow irregardless of our income level. This is important because adult learners are often faced with the problem of not having enough funds to pay for their tuition fees during registration. They have to register less number of courses initially and later during the semester (during one month after registration) they will add other courses to their list of registered courses. The purpose of the study is to determine whether the adult learners practice financial planning in their lives, to identify the sources and uses of their income/funds and to determine the learners' components of personal financial planning. The research was carried out from a quantitative perspective on 279 adult learners. Majority of the adult learners practiced personal financial planning. The main source of fund was from salary and the major use of income was for education. The components of personal financial planning were preparation of personal financial record keeping and preparation of personal financial planning.